PENGARUH MODEL PEMBELAJARAN READING QUESTIONING AND ANSWERING (RQA) BERBANTUAN APLIKASI KIPIN SCHOOL TERHADAP HASIL BELAJAR KOGNITIF SISWA KELAS VII SMP NEGERI 3 KOTA TERNATE - Ummiyati Ummiyati; Said Hasan; Bahtiar Bahtiar (JURNAL BIOEDUKASI, 2022)
The teaching and learning process is an interaction between teachers and students through reciprocal communication that takes place in an effective situation to achieve learning objectives. Entering a decade of the 21st century, the development of information and communication technology in the era of the industrial revolution 4.0 has had a significant influence on learning that must adapt and use technology in the current era, many application-based learning technologies in the field of education can be utilized by teachers as media. or tools in learning to support the teaching and learning process. The aims of this research are to determine the effect of the Reading questioning and answering learning model assisted by the Kipin School application on cognitive learning outcomes. This research is a quasi-experimental research. The sample of this study consisted of two classes, namely class VIIc as the experimental class and class VIIa as the control class with a total of 57 students. The instruments used tests to measure cognitive learning outcomes. Data analysis used the SPSS-assisted normality and homogeneity test, while the hypothesis test used anacova test and regression test. The results showed thatÂ  there was an effect of the Reading questioning and answering learning model assisted by the Kipin School application on learning outcomes. cognitive, namely with a significant value level of 0.001 0.05 .